Molecular docking of phytosterols in Stenochlaena palustris as anti-breast cancer - Dona Marisa; Lisda Hayatie; Siti Juliati; Eko Suhartono; Noer Komari (Acta Biochimica Indonesiana)
Background: Stenochlaena palustris, also known as kelakai or lemidi, is frequently linked to anti-inflammatory, anti-bacterial, anti-fungal, and antioxidant properties. S. palustris phytosterols are suggested to suppress the progression of breast cancer.